The Improvement of production capacity in small-scale industrial communities through the development of a three-phase AC motor drive system - Anggara Trisna Nugraha S.T M.T; Rama Arya Sobhita; Rachma Prilian Eviningsih; Dhadys Ayu Juli Anjhani (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2026)
This study explores the challenges of achieving precise positional control in three-phase AC motors, specifically in small industrial communities seeking to boost productivity with advanced motor systems. Although three-phase AC motors (0.25–1 kW) are efficient, they often face issues with control accuracy due to inherent inertia and long start-stop cycles. These motors typically take 1–2 seconds to reach full speed and 2–3 seconds to stop, causing disruptions in operations that require high precision and quick responses. To address these limitations, the research proposes an innovative control system designed to reduce startup time to 0.5 seconds and stopping time to 0.75 seconds. This system ensures precise positional halts, which is essential for applications such as automated production lines and specialized equipment like missile launchers. The control mechanism is fine-tuned for smooth synchronization with other subsystems, minimizing delays caused by slow motor responses. Tailored for small-scale industries, this solution tackles practical challenges by reducing downtime and improving accuracy in tasks that require short-duration actions. For example, it excels in rapid object tracking and locking, where delays could hinder target acquisition. By implementing this advanced motor control system in local industries, the research contributes to community empowerment, enhancing production efficiency, cutting operational delays, and fostering technological self-reliance. This approach highlights the transformative potential of modern motor control technology as a driver for industrial and economic growth, particularly in underserved regions where traditional systems are inadequate.